Antimicrobial Activities of Portulaca Oleracea Linn on Vitro - Ongsa kul, Metta; Sawangjaroen, Nongyao; Thaina, Peerarat; Sunbhanich, Methi; Chatbenjarong, Jindarat; Thongnurung, Aporn (Journal of Basic and Applied Pharmacology, 2015)
The in vitro antibacterial activities of Pak Bia Yai (Portulacaoleracea Linn.) were tested against Staphylococcus aureus, Escherichiacoli, Salmonella Typhimurium, Shigella sonnei and Pseudomonas aeruginosa; using Oxford Cup assay method and dilution technique method. Theantiamoebic activity was tested against Entamoeba histolytica isolated from dysenteric patients from Songklanagarin hospital. The results revealed that the plant could kill both the bacteria and the protozoa. It tis suggested that Pak Bia Yai might be an effective broad-spectrum antimicrobial agent.